1997
DOI: 10.1103/physreve.55.3124
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the rheology of dense colloidal suspensions using dissipative particle dynamics

Abstract: The rheological properties of colloidal suspensions of spheres, rods, and disks have been studied using a mesoscopic simulation technique, known as dissipative particle dynamics ͑DPD͒. In DPD, a suspension is modeled as a system of large colloidal particles in a liquid of interacting point particles. For the calculation of hydrodynamic interactions, this method is computationally more efficient than conventional techniques using a continuum model for the solvent. Applying a steady-shear rate to the particulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
218
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(220 citation statements)
references
References 48 publications
2
218
0
Order By: Relevance
“…In this work, they showed that the temperature of the system was directly related to the amplitude of the noise by means of a fluctuation dissipation theorem. Since then, DPD has been used to model wide variety of problems including, for example, shear thinning behaviour of polymer solutions [37], prediction of phase separation [38], and the suspension phenomenology of particles with different shapes [39][40][41].…”
Section: Modelling Methodologymentioning
confidence: 99%
“…In this work, they showed that the temperature of the system was directly related to the amplitude of the noise by means of a fluctuation dissipation theorem. Since then, DPD has been used to model wide variety of problems including, for example, shear thinning behaviour of polymer solutions [37], prediction of phase separation [38], and the suspension phenomenology of particles with different shapes [39][40][41].…”
Section: Modelling Methodologymentioning
confidence: 99%
“…A suspended particle of spherical/circular shape can be modelled using a single DPD particle [15][16][17][18][19]8] or a set of frozen DPD particles [20][21][22][23]. The single particle model involves three groups of DPD parameters: the first group associated with the interactions between solventsolvent particles, the second with solvent-colloidal particles and the third with colloidalcolloidal particles.…”
Section: Particulate Suspensionsmentioning
confidence: 99%
“…Applications of the technique include colloidal suspensions [4], polymer solutions [5] and binary immiscible fluids [6]. For specific applications where comparison is possible, this model is orders of magnitude faster than MD [7].…”
mentioning
confidence: 99%
“…Here the computational effort is adapted to meet the local need for detail of description: it is larger in narrow regions between the particles than in the bulk. Previous DPD simulations have had difficulty with dense colloidal suspensions precisely because the technique is unable to handle multiple lengthscale phenomena [4]. Other complex systems where modeling and simulation frequently involve several simultaneous length scales include polymeric and amphiphilic fluids, particularly in porous media and restricted geometries [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation